2010
DOI: 10.1167/iovs.09-5147
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic eNOS-Knockout Mice Develop Accelerated Retinopathy

Abstract: Diabetic eNOS(-/-) mice exhibit A significantly wider range of advanced retinal vascular complications than the age-matched diabetic C57BL/6 mice, supporting the notion that eNOS-derived NO plays an essential role in retinal vascular function. This mouse model also faithfully replicates many of the hallmarks of vascular changes associated with human retinopathy, thus providing a unique model to aid in understanding the pathologic mechanisms of and to develop effective therapeutic strategies for diabetic retino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 56 publications
6
86
0
2
Order By: Relevance
“…Increased expression of vasoactive factors and cytokines probably plays an important role in mediating the structural and functional changes in the retina [13,14]. Although recent evidence strongly suggests that inflammation is very important in the pathogenesis of early stages of experimental DR [15,16,17], studies in humans have not found a consistent association between systemic markers of inflammation and retinopathy [16,18]. Also, it is still uncertain whether inflammation plays a crucial role in the development and progression of DR in humans.…”
Section: Pathophysiology Of Drmentioning
confidence: 99%
“…Increased expression of vasoactive factors and cytokines probably plays an important role in mediating the structural and functional changes in the retina [13,14]. Although recent evidence strongly suggests that inflammation is very important in the pathogenesis of early stages of experimental DR [15,16,17], studies in humans have not found a consistent association between systemic markers of inflammation and retinopathy [16,18]. Also, it is still uncertain whether inflammation plays a crucial role in the development and progression of DR in humans.…”
Section: Pathophysiology Of Drmentioning
confidence: 99%
“…Compared to wild diabetic mice, diabetic knockout mice develop accelerated retinopathy, characterized by the formation of abnormal acellular retinal capillaries and increased retinal vascular permeability. 91 Finally, NO inhibits exocytosis of Weibel-Palade bodies by endothelial cells. Thus, in case of decreased NO availability, more von Willebrand factor and P-selectin are released making the endothelium prothrombotic.…”
Section: Disturbances Of No Availability In Early and Advanced Diabetmentioning
confidence: 99%
“…37 In brief, eyes were fixed in 4% paraformaldehyde overnight, then the retinas were dissected from eye cups, washed in water overnight, and digested in 3% trypsin (Invitrogen-Gibco, Grand Island, NY) for 3 hours at 378C. After washing with water to isolate the network of vessels from adherent retinal tissue, the vessels were mounted on a slide, allowed to dry, and stained with periodic acid Schiff-hematoxylin and eosin (Gill No.…”
Section: Trypsin Digest Preparation Of Retinal Vasculaturementioning
confidence: 99%